The Influence of Product Quality and Service on the Purchase Decision of MSME Products of Bandrek Red Ginger People in Bandar Sono Village, Nibung Hangus District, Batubara Regency - Sa'diah, Halimatun; Sari, Dian Septiana; ,, Darmilisani; Dayu, Wulan (Universitas Negeri Medan, 2024)
This research was conducted on MSMEs Personnel of Bandrek Ginger Merah which operates in the field of selling red ginger. The aim of the research to determined and analyzed the influenced of product and service quality on consumer product purchasing decisions. The population was 100 consumers who came to buy red ginger products at MSMEs, sampling was taken using random samples with saturated samples so that the total sample were 100 respondents. The type of data used was primary data and the data sources used are secondary data, data collection techniques used literature studies, surveys and observations. Data analysis techniques were multiple linear regression, classical assumption testing and hypothesis testing. The results of the research showed that the quality of products and services partially and simultaneously has positive and significant effected on consumer product purchasing decisions at MSME Insan Bandrek Jahe Merah in Bandar Sono Village, Nibung Hangus District, Batubara Regency. There was strong correlation between product and service quality and product purchasing decisions in red ginger bandrek human MSMEs. The value of R2 = 0.469 means that the decision to purchase red ginger products in the company can be explained by the quality of the product and service by 46.9% and the remaining 53.1% can be explained by other variables not studied.